Infliximab-Induced Hypothyroidism: A Novel Case and Postulations concerning the Mechanism - Brett Cerniglia; Marc A. Judson (Case Reports in Medicine)
We report a patient with cutaneous sarcoidosis who developed hypothyroidism following 17 months of infliximab therapy. To our knowledge, this is the first reported case of hypothyroidism following infliximab administration. While it is possible that the patient’s hypothyroidism was unrelated to the use of infliximab, the time course and lack of alternative explanations make such an association plausible. We postulate that hypothyroidism in this patient may have been related to the development of autoantibodies to infliximab that triggered the development of an autoimmune thyroiditis. Regardless of the mechanism, we would encourage clinicians to keep the potential mechanisms of TNF- in mind when treating patients with TNF- antagonist medications.